PERMINTAAN TENAGA KERJA PEREMPUAN PADA INDUSTRI MIKRO DAN KECIL (IMK) - Janiar Ningrum (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
The Micro and Small Industry (IMK) contributes in creating employments in the informal sector. This study analyzes demand for female workers in the IMK sectors from 2016 to 2018 which is influenced by the number of establishments, outputs, and Provincial Minimum Wages. Fixed effect models in panel data has been carried out to analyze the data. It was found that the number of businesses and the output variable had a positive and significant relationship to the demand for female workers. The coefficient value of the number of businesses is 0.5743, which means that for every one percent increase in the number of IMK establishments the demand for female labor increased by 0.5743 percent. The coefficient value of the output is 0.2046 or for every one percent increase in output the demand for female labor increased by 0.2046 percent. Meanwhile, the UMP was found to be negatively and significantly related to the demand for female labor. The UMP coefficient value is 0.5642, which means that for every one percent increase in the UMP will reduce the demand for female labor by 0.5642 percent. The increase on number of establishments and outputs on IMK will have an impact on the female workforce.